1984
DOI: 10.1111/j.1399-3054.1984.tb06075.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines bound to nucleic acids during dormancy and activation of tuber cells of Helianthus tuberosus

Abstract: Tuber tissue of Helianthus tuberosus L. (cv. OB1) contains a low amount of polyamines during dormancy but they are rapidly synthesized when tuber cells are activated in a growth medium and enter a new cell cycle. It was assumed that one of the reasons for this synthesis is that polyamines are necessary for the active conformation and correct functioning of nucleic acids. Complexes were found between spermine, spermidine and putrescine and rRNA, tRNA and an RNA fraction which contains poly(A) RNA and proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…1). Further analysis of several varieties having different ploidy is necessary to make a conclusive statement, especially as the question of polyamine binding to nucleic acids in living cells is not yet extensively investigated (Serafini-Fracassini et al 1984).…”
Section: Resultsmentioning
confidence: 99%
“…1). Further analysis of several varieties having different ploidy is necessary to make a conclusive statement, especially as the question of polyamine binding to nucleic acids in living cells is not yet extensively investigated (Serafini-Fracassini et al 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Polyamines stabilize nucleic acids [29], and are essential to steps in transcription and translation [30]. Serafini-Fracassini et al [31] suggested that newly synthesized polyamines become bound to RNA to make it active and protect RNA in vivo against stress-induced RNase activity. Inhibition of polyamine biosynthesis by DFMO may therefore affect the transcription process and consequently plant-mycorrhizal fungus interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that polyamines play a stabilizing role on nucleic acids (Bagni, Stabellini & Serafini-Fracassini, 1973) and that they are essential in every step of transcription and translation (Stevens, 1970). Recently, Serafini-Fracassini, Torrigiani & Branca (1984) suggested that newly synthesised polyamines become bound to new RNA to make it active. Furthermore, these authors also suggest that polyamines can protect RNA in vivo against stress-induced damage by inhibition of wound-induced RNase activity.…”
Section: Discussionmentioning
confidence: 99%